The genomic landscape of balanced cytogenetic abnormalities associated with human congenital anomalies - Brand, Harrison; Kammin, Tammy; Mitchell, Elyse; Hodge, Jennelle C; Hanscom, Carrie; Pillalamarri, Vamsee; Alkuraya, Fowzan S; Anderson, Mary-Anne; Antolik, Caroline; Anyane-Yeboa, Kwame; Bernstein, Jonathan A; Blumenthal, Ian; et al. (Nature genetics, 2017)
Michael Talkowski and colleagues analyze balanced chromosomal abnormalities in 273 individuals by whole-genome sequencing. Their findings suggest that sequence-level resolution improves prediction of clinical outcomes for balanced rearrangements and provides insight into pathogenic mechanisms such as altered gene regulation due to changes in chromosome topology. Despite the clinical significance of balanced chromosomal abnormalities (BCAs), their characterization has largely been restricted to cytogenetic resolution. We explored the landscape of BCAs at nucleotide resolution in 273 subjects with a spectrum of congenital anomalies. Whole-genome sequencing revised 93% of karyotypes and demonstrated complexity that was cryptic to karyotyping in 21% of BCAs, highlighting the limitations of conventional cytogenetic approaches. At least 33.9% of BCAs resulted in gene disruption that likely contributed to the developmental phenotype, 5.2% were associated with pathogenic genomic imbalances, and 7.3% disrupted topologically associated domains (TADs) encompassing known syndromic loci. Remarkably, BCA breakpoints in eight subjects altered a single TAD encompassing MEF2C , a known driver of 5q14.3 microdeletion syndrome, resulting in decreased MEF2C expression. We propose that sequence-level resolution dramatically improves prediction of clinical outcomes for balanced rearrangements and provides insight into new pathogenic mechanisms, such as altered regulation due to changes in chromosome topology.